Pansinusitis Causing Bilateral Optic Neuritis in a 9-year-old Child - Bashkaran, Karuppannan (Pusat Pengajian Sains Perubatan, 2010)
Sinusitis is a rare cause of optic neuritis in children. This case illustrntes bilateral optic neuritis in a 9-year-old child caused by pansinusi tis. It demands an accurate diagnosis with a prompt management. A proper treatment of sinusitis is essential to prevent this complication.